SUATU APLIKASI DARI PENGGABUNGAN KONSEP STRAIT FUZZY SET DAN STRAIT SOFT SET - Putri, Fadya Zahraini; Nazra, Admi; Yanita, Yanita (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This article presents an illustration of the application of combining the concepts of Strait Fuzzy Set and Strait Soft Set involving "fuzzy" and "soft" data to solve a problem in the decision-making process. From this illustration, a condition is constructed in such a way that it is possible to form a bijective Soft Set from the results of combining the two concepts of Strait Fuzzy Set and Strait Soft Set. This research is descriptive qualitative research with a case study approach. An interesting result of this study is that for each parameter it is possible that there is only one group of objects that excel at certain parameters from all the existing parameters